Annotated checklist of Albanian butterflies (Lepidoptera, Papilionoidea and Hesperioidea) - Rudi Verovnik; Miloš Popović (ZooKeys, 2013)
The Republic of Albania has a rich diversity of flora and fauna. However, due to its political isolation, it has never been studied in great depth, and consequently, the existing list of butterfly species is outdated and in need of radical amendment. In addition to our personal data, we have studied the available literature, and can report a total of 196 butterfly species recorded from the country. For some of the species in the list we have given explanations for their inclusion and made other annotations. Doubtful records have been removed from the list, and changes in taxonomy have been updated and discussed separately. The purpose of our paper is to remove confusion and conflict regarding published records. However, the revised checklist should not be considered complete: it represents a starting point for further research.